2014
DOI: 10.1002/bit.25179
|View full text |Cite
|
Sign up to set email alerts
|

Cell cultivation under different gravitational loads using a novel random positioning incubator

Abstract: Important in biotechnology is the establishment of cell culture methods that reflect the in vivo situation accurately. One approach for reaching this goal is through 3D cell cultivation that mimics tissue or organ structures and functions. We present here a newly designed and constructed random positioning incubator (RPI) that enables 3D cell culture in simulated microgravity (0 g). In addition to growing cells in a weightlessness-like environment, our RPI enables long-duration cell cultivation under various g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…We have recently reported another approach to upgrading the RPM by installing a commercial CO 2 incubator onto the rotating frames. This RPM, called “random positioning incubator” (RPI) [ 9 , 10 ], has the advantage of being independent of large laboratory incubators ( Figure 1 ). Furthermore, the closed chamber of the incubator isolates the environment of the culture flasks and thus prevents exposure of biological samples to vapor and wear from the machinery, for example, [ 10 ].…”
Section: Rpm Development and Technologymentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently reported another approach to upgrading the RPM by installing a commercial CO 2 incubator onto the rotating frames. This RPM, called “random positioning incubator” (RPI) [ 9 , 10 ], has the advantage of being independent of large laboratory incubators ( Figure 1 ). Furthermore, the closed chamber of the incubator isolates the environment of the culture flasks and thus prevents exposure of biological samples to vapor and wear from the machinery, for example, [ 10 ].…”
Section: Rpm Development and Technologymentioning
confidence: 99%
“…We have also been working on an upgrade of the software responsible for controlling the motion of the RPM. Three different algorithms were introduced recently that simulated partial Earth gravity (0 to 0.6 g), allowing simulation of moon- or Mars-like gravity conditions [ 9 ]. All algorithms are adaptations of the random walk algorithm originally designed to simulate microgravity [ 10 ].…”
Section: Partial Earth Gravity Loadmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we have also shown that hypergravity at 4 g does not affect myoblast proliferation or cell cycle progression. Furthermore, by using a novel RPM that simulates partial gravity, we observed a linear correlation between the slowed cell growth and the accumulation in the G2/M phase corresponding to the partial gravity level of exposure [88]. We attribute these effects to an impaired regulation of calcium through mechanosensitive channels disturbed by the removal of the force of gravity.…”
Section: Myogenic Responses: Cell Cycle Proliferation Differentiatimentioning
confidence: 99%